2007
DOI: 10.1111/j.1365-2982.2007.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid type 1 receptor modulates intestinal propulsion by an attenuation of intestinal motor responses within the myenteric part of the peristaltic reflex

Abstract: Cannabinoid-1 (CB1) receptor activation affects gastrointestinal propulsion in vivo. It was our aim to further characterize the involved myenteric mechanisms in vivo and in vitro. In CB1(-/-) mice and wild-type littermates we performed in vivo transit experiments by charcoal feeding and in vitro electrophysiological recordings in mouse small intestinal smooth muscle. Ascending neuronal contraction (ANC) following electrical field stimulation was studied in rat ileum in a partitioned organ bath separating the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 41 publications
8
37
0
Order By: Relevance
“…7C) compared with the vehicle control group. In CB 1 receptordeficient mice, transit times were accelerated compared with wild-type mice, in agreement with previous reports (48). The inhibitory action of 40 mg/kg URB602 on whole gut transit was absent in these mice (Fig.…”
Section: Resultssupporting
confidence: 92%
“…7C) compared with the vehicle control group. In CB 1 receptordeficient mice, transit times were accelerated compared with wild-type mice, in agreement with previous reports (48). The inhibitory action of 40 mg/kg URB602 on whole gut transit was absent in these mice (Fig.…”
Section: Resultssupporting
confidence: 92%
“…As shown in the present study and by others (15,21,28,29,35), the cannabinoids are potent inhibitors of peristaltic propulsion. This has largely been attributed to inhibition of the ascending contraction component as a result of CB-1 receptormediated inhibition of acetylcholine release.…”
Section: Discussionsupporting
confidence: 85%
“…ACh is one of the primary transmitters released from the excitatory motor neurons innervating the circular muscle layer, suggesting that cannabinoids might inhibit the ascending contraction limb of the peristaltic reflex. Previous studies by others have examined this and shown convincingly that the ascending contraction limb of the peristaltic reflex is inhibited by cannabinoids acting at cholinergic excitatory motor neurons and/or ascending excitatory interneurons (15,29,32,35). Similarly, a variety of CB-1 antagonists have been shown to enhance the ascending limb of the peristaltic reflex, suggesting a restraining influence of endocannabinoids.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Thus CB1 receptors also modulate intestinal propulsion by an attenuation of the peristaltic reflex (30).…”
Section: Discussionmentioning
confidence: 99%